The Relationship Between Exclusive Breastfeeding And Complementary Feeding With The Incidence Of Stunting Babies Under Two Years In Mandailing Natal Districts North Sumatra - Zuraidah Nasution; Mahdiah Mahdiah; Ida Nurhayati; Ratna Zahara; Evi Irianti; Tetty Herta Doloksaribu (Syntax Corporation Indonesia, 2023)
Background: Stunting is a condition in which growth and development is disrupted by children caused by chronic malnutrition. This study aims to determine the relationship between exclusive breastfeeding and the age of complementary feeding (MP-ASI) with the incidence of stunting. This study uses a quantitative approach with secondary data analysis and tested by chi-square with the sample. The statistical results show a value of p = 0.05. This study can be concluded that there is a relationship between the age of complementary feeding (MP-ASI) and the incidence of stunting. In other words, it is said that the sooner prelactal food is given, the easier it is for stunting to occur in children aged 0-2 years. The statistical results show p = 1,000, this shows that there is no relationship between exclusive breastfeeding and the incidence of stunting